CXCL10 is upregulated in synovium and cartilage following articular fracture. Issue 4 (20th November 2017) - Furman, Bridgette D.; Kent, Collin L.; Huebner, Janet L.; Kraus, Virginia B.; McNulty, Amy L.; Guilak, Farshid; Olson, Steven A.
ABSTRACT: The objective of this study was to investigate the expression of the chemokine CXCL10 and its role in joint tissues following articular fracture. We hypothesized that CXCL10 is upregulated following articular fracture and contributes to cartilage degradation associated with post‐traumatic arthritis (PTA). To evaluate CXCL10 expression following articular fracture, gene expression was quantified in synovial tissue from knee joints of C57BL/6 mice that develop PTA following articular fracture, and MRL/MpJ mice that are protected from PTA. CXCL10 protein expression was assessed in human cartilage in normal, osteoarthritic (OA), and post‐traumatic tissue using immunohistochemistry. The effects of exogenous CXCL10, alone and in combination with IL‐1, on porcine cartilage explants were assessed by quantifying the release of catabolic mediators. Synovial tissue gene expression of CXCL10 was upregulated by joint trauma, peaking one day in C57BL/6 mice (25‐fold) versus 3 days post‐fracture in MRL/MpJ mice (15‐fold). CXCL10 protein in articular cartilage was most highly expressed following trauma compared with normal and OA tissue. In a dose dependent manner, exogenous CXCL10 significantly reduced total matrix metalloproteinase (MMP) and aggrecanase activity of culture media from cartilage explants. CXCL10 also trended toward a reduction in IL‐1α‐stimulated total MMP activity ( p  = 0.09) and S‐GAG ( p  = 0.09), but not NO release. In conclusion, CXCL10 was upregulated in synovium and chondrocytes following trauma. However, exogenous CXCL10 did not induce a catabolic response in cartilage. CXCL10 may play a role in modulating the chondrocyte response to inflammatory stimuli associated with joint injury and the progression of PTA. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1220–1227, 2018. Abstract : The objective of this study was to investigate the chemokine CXCL10 and its role in joint tissues following articular fracture. We hypothesized that CXCL10 is upregulated following articular fracture and contributes to cartilage degradation associated with post‐traumatic arthritis (PTA). CXCL10 was upregulated in synovium and chondrocytes (see legend Fig. 2) following trauma, but did not directly induce catabolism of articular cartilage. Findings from this study suggest that CXCL10 may play a role in homeostasis of chondrocytes and modulation of inflammation.